Combination of microbubbles and diagnostic ultrasound at a high mechanical index for the synergistic microwave ablation of tumours. (3rd April 2017) - Xu, Jinshun; Cao, Yang; Xu, Chunyan; Cheng, Xueqing; You, Yufeng; Yao, Yuanzhi; Liu, Jianxin; Wang, Zhigang; Li, Pan; Lu, Min
Abstract: Objectives: To determine whether combining microbubbles (MBs) with diagnostic ultrasound (US) at a high mechanical index (MI) could enhance the microwave (MW) ablation of tumours. Materials and methods: Five therapeutic MW adjuvant protocols were studied: MW, MW + US, MW + US + MB, MW + US + NS (saline) and MW + MB. In 30 normal rabbit livers, the synergistic effects were evaluated via temperature, necrosis volume and histology. In 90 VX2 rabbit hepatic tumours, residual cells in the peripheral ablated tumours were examined via immunohistochemical assay and tumour growth. Additional 40 VX2 hepatic tumours were evaluated for ablation safety via blood assay and weight and for survival to 105 days. Results were compared using analysis of variance. Results: Compared with the other protocols, the ablation volumes in normal rabbit livers were significantly larger using the MW + US + MB protocol ( p  < .001). The histological examination was consistent with more efficient ablation in that protocol. In detecting residual cells, the apoptotic index was higher, the proliferating index was lower ( p  < .05), tumour growth was significantly smaller ( p  < .001), and the rabbits of the MW + US + MB T-Group survived longer ( p  < .05) than those of the other groups. Additionally, no damage to the liver function or blood cells was found in any of the protocols after ablation ( p  < .05). Conclusions: MBs in combination with diagnostic US at a high MI showed potential synergy in the MW ablation of tumours in rabbits.